Vitamin E intake and risk of stroke: a meta-analysis. Issue 10 (7th November 2018) - Cheng, Pengfei; Wang, Lihua; Ning, Shujun; Liu, Zichun; Lin, Hao; Chen, Shuli; Zhu, Jiaying
Abstract: Findings from observational studies on the associations between vitamin E intake and stroke risk remain controversial, and the dose–response relationship between vitamin E intake and risk of stroke remains to be determined. We conducted a meta-analysis of prospective studies aiming to clarify the relationships between vitamin E intake and risk of stroke. Relevant studies were identified by searching online databases through to June 2018. We computed summary relative risks (RR) with corresponding 95 % CI. Among 3156 articles retrieved from online databases and relevant bibliographies, nine studies involving 3284 events and 220 371 participants were included in the final analyses. High dietary vitamin E intake was inversely associated with the risk of overall stroke (RR=0·83, 95 % CI 0·73, 0·94), and with the risk of stroke for individuals who were followed-up for <10 (RR=0·84, 95 % CI 0·72, 0·91). There was a non-linear association between dietary vitamin E intake and stroke risk ( P =0·0249). Omission of any single study did not alter the summary result. In conclusion, this meta-analysis suggests that there is a significant inverse relationship between dietary vitamin E intake and stroke risk. This meta-analysis provides evidence that a higher dietary vitamin E intake is associated with a lower stroke risk.